A New Source of Inoculum for Stemphylium vesicarium: Consequences for the Management of Brown Spot of Pear - Federico Cavina; Serena Baiocco; Lorenzo Tomba; Fabio Ravaglia; Christian Moretti; Rosario Raso; Valentino Giorgio Rettore; Martina Parrilli; Gianfranco Pradolesi; Riccardo Bugiani (Agronomy)
Brown spot of pear (BSP), caused by Stemphylium vesicarium, is one of the most dangerous pear fungal diseases, being responsible for huge losses in production. Currently, in order to increase its containment, chemical control is implemented in conjunction with agronomic techniques able to reduce BSP inoculum sources (e.g., orchard grass sanitation, litter removal or application of biocontrol agents). Regardless, despite the introduction of agronomic practices, the complete control of the disease is still rarely possible, which suggests that other sources of S. vesicarium inoculum that are currently neglected may be involved. The aim of this study is to investigate the possible wintering forms of Pleospora allii/S. vesicarium on pear wood and whether any spore-forming productions (conidial or ascosporic) might infect the green tissues of the plant in the following spring. Symptomatic fragments of woody tissue from a commercial pear orchard (in Ferrara, Emilia-Romagna, Italy) with a high BSP pressure (~40% incidence) were analysed. The results prove that pseudothecia and the maturation of ascospores of P. allii also develop on one-year-old branch cankers of pear trees, thus representing an additional source of inoculum. In conclusion, the pruning of affected branches and removal of relative residues should be preventatively performed in order to improve BSP management and control.